A Resource for Guiding Data Stewards to Make European Rare Disease Patient Registries FAIR - van Damme, Philip; Moreno, Pablo Alarcón; Bernabé, César H.; Ballesteros, Alberto Cámara; Le Cornec, Clémence M. A.; Dos Santos Vieira, Bruna; van der Velde, K. Joeri; Zhang, Shuxin; Carta, Claudio; Cornet, Ronald; ’t Hoen, Peter A.C.; Jacobsen, Annika; et al. (Data science journal, 2023)
Objective: This paper reports on the development of a dynamic data management planning questionnaire to guide data stewards of the European Reference Network (ERN) rare disease patient registries to make their data findable, accessible, interoperable, and reusable (FAIR). As part of this work, the questionnaire was validated through expert review and aligned with existing resources on rare diseases and FAIR data management. Materials and Methods: The questionnaire was developed for the Data Stewardship Wizard, a tool for data management planning. Knowledge sources on FAIR data, ERN patient registries, and data management were used to compose questions. Ten domain experts validated the questionnaire. The topics in the questionnaire were aligned with existing knowledge bases. Results: A total of 57 questions were included in the questionnaire. Twenty-three references to the FAIR Cookbook and Research Data Management toolkit for Life Sciences were added. Expert validation provided a total of 166 comments on content, structure, and software-related issues. A public instance of the Data Stewardship Wizard was deployed for use by data stewards of ERN patient registries. Discussion: The questionnaire addresses issues that ERNs encounter when making their registries FAIR and follows the implementation choices made by the European rare disease community. A challenging task for future research is to extend the questionnaire to other types of registries and to validate with users. Conclusion: This smart questionnaire is the first model created for the Data Stewardship Wizard that helps ERN patient registries with making their data FAIR. It will assist data stewards in aligning their efforts and providing guidance on FAIR data.